Cloud intrusion detection systems: fuzzy logic and classifications - Alqahtani, Saeed Masaud H. (2017)
Cloud Computing (CC), as defned by national Institute of Standards and Technology (NIST), is a new technology model for enabling convenient, on-demand network access to a shared pool of configurable computing resources such as networks, servers, storage, applications, and services that can be rapidly provisioned and released with minimal management effort or service-provider interaction. CC is a fast growing field; yet, there are major concerns regarding the detection of security threats, which in turn have urged experts to explore solutions to improve its security performance through conventional approaches, such as, Intrusion Detection System (IDS). In the literature, there are two most successful current IDS tools that are used worldwide: Snort and Suricata; however, these tools are not flexible to the uncertainty of intrusions. The aim of this study is to explore novel approaches to uplift the CC security performance using Type-1 fuzzy logic (T1FL) technique with IDS when compared to IDS alone. All experiments in this thesis were performed within a virtual cloud that was built within an experimental environment. By combining fuzzy logic technique (FL System) with IDSs, namely SnortIDS and SuricataIDS, SnortIDS and SuricataIDS for detection systems were used twice (with and without FL) to create four detection systems (FL-SnortIDS, FL-SuricataIDS, SnortIDS, and SuricataIDS) using Intrusion Detection Evaluation Dataset (namely ISCX). ISCX comprised two types of traffic (normal and threats); the latter was classified into four classes including Denial of Service, User-to-Root, Root-to-Local, and Probing. Sensitivity, specificity, accuracy, false alarms and detection rate were compared among the four detection systems. Then, Fuzzy Intrusion Detection System model was designed (namely FIDSCC) in CC based on the results of the aforementioned four detection systems. The FIDSCC model comprised of two individual systems pre-and-post threat detecting systems (pre-TDS and post-TDS). The pre-TDS was designed based on the number of threats in the aforementioned classes to assess the detection rate (DR). Based on the output of this DR and false positives of the four detection systems, the post-TDS was designed in order to assess CC security performance. To assure the validity of the results, classifier algorithms (CAs) were introduced to each of the four detection systems and four threat classes for further comparison. The classifier algorithms were OneR, Naive Bayes, Decision Tree (DT), and K-nearest neighbour. The comparison was made based on specific measures including accuracy, incorrect classified instances, mean absolute error, false positive rate, precision, recall, and ROC area. The empirical results showed that FL-SnortIDS was superior to FL-SuricataIDS, SnortIDS, and SuricataIDS in terms of sensitivity. However, insignificant difference was found in specificity, false alarms and accuracy among the four detection systems. Furthermore, among the four CAs, the combination of FL-SnortIDS and DT was shown to be the best detection method. The results of these studies showed that FIDSCC model can provide a better alternative to detecting threats and reducing the false positive rates more than the other conventional approaches.